Thiết kế hoạt động dạy học tích hợp trong môn Ngữ văn 10 bằng mô hình “Lớp học đảo ngược” - Nguyễn, Chí Nguyện; Lê, Thị Thơm (Tạp chí Giáo dục, 2025)
The requirement for integrated teaching has been clearly stated in the 2018 General Education Program in most subjects. Research on the integration of Literature with History and Geography shows that the connection of knowledge in these three fields is completely reasonable and brings certain effectiveness. Based on the theoretical basis and through a specific document, the article aims to show that integrated teaching helps learners grasp the breadth and depth of knowledge, knowledge is deeply engraved in the process of discovery and acquisition through integration in subjects. This combination not only meets the requirements within the scope of Literature but is also a way to expand and connect with other subjects, especially subjects in the field of social sciences.